Toenail Onychomycosis—A Canadian Approach With a New Transungual Treatment: Development of a Clinical Pathway. Issue 5 (September 2015) - Gupta, Aditya K.; Sibbald, R. Gary; Andriessen, Anneke; Belley, Richard; Boroditsky, Alan; Botros, Mariam; Chelin, Robert; Gulliver, Wayne; Keast, David; Raman, Mani
Background: Onychomycosis is a difficult-to-treat infection whose current treatment paradigm relies primarily on oral antifungals. The emergence of new topical drugs broadens the therapeutic options and prompts a re-evaluation of the current Canadian treatment strategy. Objective: To define a patient-centred Canadian treatment strategy for onychomycosis. Methods: An expert panel of doctors who treat onychomycosis was convened. A systematic review of the literature on treatments for onychomycosis was conducted. Based on the results, a survey was designed to determine a consensus treatment system. Results: First-line therapy should be selected based on nail plate involvement, with terbinafine for severe onychomycosis (>60% involvement), terbinafine or efinaconazole for moderate onychomycosis (20%-60% involvement), and efinaconazole for mild onychomycosis (<20% involvement). Comorbidities, patient preference and adherence, or nail thickness may result in the use of alternative oral or topical antifungals. Conclusion: These guidelines allow healthcare providers and patients to make informed choices about preventing and treating onychomycosis.